Research progress and materials selection guidelines on mixed conducting perovskite-type ceramic membranes for oxygen production - Zhang, K.; Sunarso, J.; Shao, Z.; Zhou, W.; Sun, C.; Wang, Shaobin; Liu, Shaomin (Royal Society of Chemistry, 2011)
Oxygen production by air separation is of great importance in both environmental and industrial processes as most large scale clean energy technologies require oxygen as feed gas. Currently the conventional cryogenic air separation unit is a major economic impediment to the deployment of these clean energy technologies with carbon capture (i.e. oxy-fuel combustion). Dense ceramic perovskite membranes are envisaged to replace the cryogenics and reduce O2 production costs by 35% or more; which can significantly cut the energy penalty by 50% when integrated in oxy-fuel power plant for CO2 capture. This paper reviews the current progress in the development of dense ceramic membranes for oxygen production. The principles, advantages or disadvantages, and the crucial problems of all kinds of membranes are discussed. Materials development, optimisation guidelines and suggestions for future research direction are also included. Some areas already previously reviewed are treated with less attention.